The Involvement of Limb Muscle Explosive Power and Body Flexure on Front Kick Acceleration - Sinaga, Victor; Lanos, Muhsana El Cintami; Setiawan, Sigit Budi; Apriyadi, Irwansyah; Rohayu, Septiani; Sanopa, Dedi Fuad (Universitas PGRI Palembang, 2023)
The problem of this research is the low ability of the front kick of UNP martial arts athletes. The purpose of this study was to find out: 1) how much the contribution of leg muscle explosive power to the speed of the front kick of pencak silat athletes at Padang State University, 2) how much the contribution of body flexibility to the speed of the front kick of pencak silat athletes at Padang State University, 3) how much the contribution of leg muscle explosive power and body flexibility to the speed of the front kick of pencak silat athletes at Padang State University. This research is correlational, which is to find out how much the relationship of variables with one another. The population in this study was atlet pencak silat UNP, and untill amounted to 20 people who were carried out at the Lubuk Buaya PGSD Campus using purposive sampling techniques , namely sampling based on the researchers' considerations. Based on the calculation of product moment correlation, 1) There is a significant contribution to the explosive power of the leg muscles with the kick speed of UNP pencak silat athletes of 22.66%, 2) There is a significant contribution of body flexibility with the kick speed of UNP pencak silat athletes of 25.7%, 3) There is a contribution which is significant, the explosive power of the leg muscles and flex with the ability of the kick speed of UNP martial arts athletes by 30.25%. This shows that the improvement to the speed of the front kick of UNP Padang pencak silat athletes can be done by making improvements to thelegs and flexibility of the athlete's body.